2008
DOI: 10.1093/schbul/sbn040
|View full text |Cite
|
Sign up to set email alerts
|

Major Self-mutilation in the First Episode of Psychosis

Abstract: Major self-mutilation (MSM) is a rare but catastrophic complication of severe mental illness. Most people who inflict MSM have a psychotic disorder, usually a schizophrenia spectrum psychosis. It is not known when in the course of psychotic illness, MSM is most likely to occur. In this study, the proportion of patients in first episode of psychosis (FEP) was assessed using the results of a systematic review of published case reports. Histories of patients who had removed an eye or a testicle, severed their pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
128
0
16

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(150 citation statements)
references
References 84 publications
(25 reference statements)
1
128
0
16
Order By: Relevance
“…We also found that previous suicide attempts were associated with violence risk. Although high levels of self-harm and suicide attempts are reported in individuals with psychosis [56], less research has focused on the relationship between suicide risk and violence in psychosis. Commonly used violence risk assessment instruments, however, do not routinely include assessment of suicide risk and may need revision in the light of this review.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that previous suicide attempts were associated with violence risk. Although high levels of self-harm and suicide attempts are reported in individuals with psychosis [56], less research has focused on the relationship between suicide risk and violence in psychosis. Commonly used violence risk assessment instruments, however, do not routinely include assessment of suicide risk and may need revision in the light of this review.…”
Section: Discussionmentioning
confidence: 99%
“…Most people who perform MSM have a psychotic disorder. 11 Similarly, self-castration usually occurs in transsexualism, serious personality disorders and psychosis. 12 Aboseif et al reported 14 patients with 19 self-inflicted genital injuries, 65% were psychotic while 35% were not.…”
Section: Discussionmentioning
confidence: 99%
“…They often result in permanent loss of an organ or its function. [5,6] Self-mutilation resulting in an amputated extremity is rare. They lead to a difficult decision for the treating doctors as evidence shows that favourable functional outcomes post replantation requires good postoperative rehabilitation with a motivated patient.…”
Section: Introductionmentioning
confidence: 99%